2020
DOI: 10.1093/nar/gkaa850
|View full text |Cite
|
Sign up to set email alerts
|

LncExpDB: an expression database of human long non-coding RNAs

Abstract: Expression profiles of long non-coding RNAs (lncRNAs) across diverse biological conditions provide significant insights into their biological functions, interacting targets as well as transcriptional reliability. However, there lacks a comprehensive resource that systematically characterizes the expression landscape of human lncRNAs by integrating their expression profiles across a wide range of biological conditions. Here, we present LncExpDB (https://bigd.big.ac.cn/lncexpdb), an expression database of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 48 publications
2
66
0
Order By: Relevance
“…LncExpDB ( https://bigd.big.ac.cn/lncexpdb ; detailed in ( 10 ) in this issue) is an expression database of human long non-coding RNAs (lncRNAs). Based on our previous work on LncBook ( 11 ), LncExpDB houses abundant expression profiles of 101 293 non-redundant, manually-curated lncRNA genes across 337 biological conditions, which can be further classified into nine important biological contexts, namely, normal tissue/cell line, cancer cell line, subcellular localization, exosome, cell differentiation, preimplantation embryo, organ development, circadian rhythm, and virus infection.…”
Section: New Databasesmentioning
confidence: 99%
“…LncExpDB ( https://bigd.big.ac.cn/lncexpdb ; detailed in ( 10 ) in this issue) is an expression database of human long non-coding RNAs (lncRNAs). Based on our previous work on LncBook ( 11 ), LncExpDB houses abundant expression profiles of 101 293 non-redundant, manually-curated lncRNA genes across 337 biological conditions, which can be further classified into nine important biological contexts, namely, normal tissue/cell line, cancer cell line, subcellular localization, exosome, cell differentiation, preimplantation embryo, organ development, circadian rhythm, and virus infection.…”
Section: New Databasesmentioning
confidence: 99%
“…Many free online databases and programs can help to predict the function of identified lncRNAs or circRNAs in cancer development and progression. These include AnnoLnc2 for human lncRNAs annotation [ 229 ], LNCipedia, a comprehensive compendium of human long non-coding RNAs [ 230 ], LncExpDB, an expression database of human lncRNA genes [ 231 ], LincSNP 3.0, a database for single nucleotide polymorphisms (SNPs) in human lncRNAs [ 232 ], lnCAR, a comprehensive resource for lncRNAs in cancers [ 233 ], or databases for circular RNAs such as circBASE [ 234 ] or circInteractome [ 235 ]. Sun et al have identified 246 differentially-expressed lncRNAs in metastatic melanoma cell lines when compared to primary melanomas [ 236 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…LncExpDB was released by China’s National Bio-Information Center in 2020 ( 68 ). The database contains the expression of the lncRNA genes from 101 293 individuals in 337 biological environments and 1977 samples under nine biological conditions.…”
Section: General Platformsmentioning
confidence: 99%
“…On the interface, users can browse the expressions of interested lncRNAs in nine different biological contexts, including cancer tissue/cell lines, normal tissue/cell line, exosome, cell differentiation, subcellular localization, preimplantation embryo, organ development, virus infection and circadian rhythm. Based on a large amount of RNA-seq data, a total of 2907 cancer cells were identified, and oncologists were able to estimate the expression of the lncRNA’s biological function in cancer cells ( 68 ). In the cancer cell line option in the context module, the visual expression of interested lncRNA can be gained in cancer cell line.…”
Section: General Platformsmentioning
confidence: 99%